Mutational Profile and Clonal Evolution of Relapsed/Refractory Diffuse Large B-Cell Lymphoma - Lee, Boram; Lee, Hyunwoo; Cho, Junhun; Yoon, Sang Eun; Kim, Seok Jin; Park, Woong-Yang; Kim, Won Seog; Ko, Young Hyeh (Frontiers in Oncology, 2021)
Primary refractory/relapsed diffuse large B-cell lymphoma (rrDLBCL) is an unresolved issue for DLBCL treatment and new treatments to overcome resistance is required. To explore the genetic mechanisms underlying treatment resistance in rrDLBCL and to identify candidate genes, we performed targeted deep sequencing of 430 lymphoma-related genes from 58 patients diagnosed with rrDLBCL. Genetic alterations found between the initial biopsy and biopsy at recurrence or refractory disease were investigated. The genes most frequently altered (> 20%) were (in decreasing order of frequency) CDKN2A, PIM1, CD79B, TP53, MYD88, MYC, BTG2, BTG1, CDKN2B, DTX1, CD58, ETV6, and IRF4. Genes mutation of which in pretreatment sample were associated with poor overall survival included NOTCH1, FGFR2, BCL7A, BCL10, SPEN and TP53 (P < 0.05). FGFR2, BCL2, BCL6, BCL10 and TP53 were associated with poor progression-free survival (P < 0.05). Most mutations were truncal and were maintained in both the initial biopsy and post-treatment biopsy with high dynamics of subclones. Immune-evasion genes showed increased overall mutation frequency (CD58, B2M) and variant allele fraction (CD58), and decreased copy number (B2M, CD70) at the post-treatment biopsy. Using the established mutational profiles and integrative analysis of mutational evolution, we identified information about candidate genes that may be useful for the development of future treatment strategies.